SCHOOL LEADERSHIP AND POLICY IN IMPLEMENTING UNDERSTANDING BY DESIGN: A COMPARATIVE CASE STUDY IN ENGLISH TEACHING MODULES - Retnowati, Nanik; Pham Thi Thu Hien; Maulidia Rachmawati Nur; Linda; Tsaniatul Fatiha; Lutfio Indra Permana (University of Kuningan, 2025)
Effective teaching relies heavily on intentional instructional planning that aligns learning goals, assessments, and activities. The Understanding by Design (UbD) framework, known for its backward design approach, has been adopted within Indonesia’s Merdeka Curriculum to promote coherence and purpose in learning. However, its implementation across schools varies significantly, often shaped by leadership practices and local policy enforcement. This study investigates how school leadership influences the implementation of UbD in English teaching modules at two public secondary schools in Bogor City. Employing qualitative content analysis, the research draws on data from curriculum documents, semi-structured teacher interviews, and classroom observations. Findings reveal that one school demonstrates effective UbD integration, driven by assertive leadership, clear policy communication, and routine monitoring. In contrast, the second school shows fragmented implementation due to limited leadership involvement and a lack of institutional reinforcement. These contrasting cases highlight that while teacher understanding is necessary, school leadership plays a pivotal role in translating national curriculum mandates into coherent instructional practice. The study underscores the importance of proactive leadership and coordinated policy support to ensure the consistent and meaningful adoption of curriculum frameworks like UbD in schools.